(untitled) (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Poor inhalation technique among patients using Metered Dose Inhaler (MDI) is one of the most common causes of increased acute exacerbations and hospital visits and leads to poor health outcome. Hence, the purpose of this research is to evaluate the correctness of inhalation steps in patients using MDI visiting Patan Hospital. Method: A total of 128 patients participated in the research. The study involved collection of basic sociodemographic information and visual observation of the inhalation technique of the patients using a standard checklist. Any mistakes made during the procedure were recorded. They were also asked to say each step as they performed it so that all of the steps could be clearly observed. Result: Out of 128 participants, only 3(2.34%) of the participants were able to perform all the eight steps correctly. Holding breath for five second was the most commonly made mistake 80(62.7%) followed by failure to exhale to residual volume 74(57.7%). Majority of participants were able to perform five steps correctly 29(22.6%). There seemed to be no association of inhalation technique with age, sex and educational status of the patient. Conclusion: Majority of the patients were unable to perform the inhalation steps correctly indicating the need for regular training programs to improve the inhalation technique and improve health outcome.